A new device for estimating active drag in swimming at maximal velocity - Xin-Feng, W.; Lian-Ze, W.; Wei-Xing, Y.; De-Jian, L.; Xiong, S. (Journal of Sports Sciences, 2007)
A new device was designed to measure the active drag during maximal velocity swimming based on the assumption of equal useful power output in two cases: with and without a small additional drag. A gliding block was used to provide an adjustable drag, which was attached to the swimmer and measured by a force transducer. Six swimmers of national standard (3 males, 3 females) participated in the test. For the males, the mean active drag ranged from 48.57 to 105.88 N in the front crawl and from 54.14 to 76.37 N in the breaststroke. For the females, the mean active drag ranged from 36.31 to 50.27 N in the front crawl and from 36.25 to 77.01 N in the breaststroke. During testing, the swimmer's natural stroke and kick were not disturbed. We conclude that the device provides a useful method for measuring and studying active drag.